Effect of Deposited Stannous Chloride on the Flame-Retardancy Imparted to Cotton Fabric - Morteza Mostashari, Seyed (Asian Journal of Chemistry, 2016)
The effect of stannous chloride as a non-durable finish on the flammability of 100% cotton fabric (cotton woven construction, weighing 178 g/m2) has been investigated. The laundered bone-dried weighed fabrics were impregnated with suitable concentrations of aqueous stannous chloride solutions by means of squeeze rolls and dried at 65°C for 4 h. Afterwards they were cooled in a desiccator, weighed with analytical precision and kept under ordinary conditions before the fulfillment of the vertical flame test. The optimum add-on values to impart flame retardancy expressed in g anhydrous salt per 100 g fabric was about 5.0-7.71 g. The results with the impartation of stannous chloride into the cotton fabric are in favour of Free Radical Theory and also Vapour Phase Theory.